Mitochondrial dysfunction causes Ca2+ overload and ECM degradation–mediated muscle damage in C. elegans. Issue 8 (4th June 2019) - Sudevan, Surabhi; Takiura, Mai; Kubota, Yukihiko; Higashitani, Nahoko; Cooke, Michael; Ellwood, Rebecca A.; Etheridge, Timothy; Szewczyk, Nathaniel J.; Higashitani, Atsushi
ABSTRACT: Mitochondrial dysfunction impairs muscle health and causes subsequent muscle wasting. This study explores the role of mitochondrial dysfunction as an intramuscular signal for the extracellular matrix (ECM)–based proteolysis and, consequentially, muscle cell dystrophy. We found that inhibition of the mitochondrial electron transport chain causes paralysis as well as muscle structural damage in the nematode Caenorhabditis elegans . This was associated with a significant decline in collagen content. Both paralysis and muscle damage could be rescued with collagen IV overexpression, matrix metalloproteinase (MMP), and Furin inhibitors in Antimycin A–treated animal as well as in the C. elegans Duchenne muscular dystrophy model. Additionally, muscle cytosolic calcium increased in the Antimycin A–treated worms, and its down‐regulation rescued the muscle damage, suggesting that calcium overload acts as one of the early triggers and activates Furin and MMPs for collagen degradation. In conclusion, we have established ECM degradation as an important pathway of muscle damage.—Sudevan, S., Takiura, M., Kubota, Y., Higashitani, N., Cooke, M., Ellwood, R. A., Etheridge, T., Szewczyk, N. J., Higashitani, A. Mitochondrial dysfunction causes Ca 2+ overload and ECM degradation–mediated muscle damage in C. elegans . FASEB J. 33, 9540–9550 (2019). www.fasebj.org